A novel role for junctional adhesion molecule‐A in tumor proliferation: Modulation by an anti‐JAM‐A monoclonal antibody. Issue 6 (13th December 2012) - Goetsch, Liliane; Haeuw, Jean‐François; Beau‐Larvor, Charlotte; Gonzalez, Alexandra; Zanna, Laurence; Malissard, Martine; Lepecquet, Anne‐Marie; Robert, Alain; Bailly, Christian; Broussas, Matthieu; Corvaia, Nathalie
Abstract: To identify new potential targets in oncology, functional approaches were developed using tumor cells as immunogens to select monoclonal antibodies targeting membrane receptors involved in cell proliferation. For that purpose cancer cells were injected into mice and resulting hybridomas were screened for their ability to inhibit cell proliferation in vitro. Based on this functional approach coupled to proteomic analysis, a monoclonal antibody specifically recognizing the human junctional adhesion molecule‐A (JAM‐A) was defined. Interestingly, compared to both normal and tumor tissues, we observed that JAM‐A was mainly overexpressed on breast, lung and kidney tumor tissues. In vivo experiments demonstrated that injections of anti‐JAM‐A antibody resulted in a significant tumor growth inhibition of xenograft human tumors. Treatment with monoclonal antibody induced a decrease of the Ki67 expression and downregulated JAM‐A levels. All together, our results show for the first time that JAM‐A can interfere with tumor proliferation and suggest that JAM‐A is a potential novel target in oncology. The results also demonstrate that a functional approach coupled to a robust proteomic analysis can be successful to identify new antibody target molecules that lead to promising new antibody‐based therapies against cancers. Abstract : What's new? Discovering novel therapeutic targets is a crucial challenge in oncology research. In this study, the authors used a functional approach, seeking monoclonal antibodies that could inhibit cancer‐cell proliferation. They injected whole cancer cells into mice, screened the resulting monoclonals in vitro, then used proteomic analysis to identify the target antigens. A monoclonal antibody against the tight‐junction protein JAM‐A was able to slow the growth of xenograft human tumours in mice. This approach may aid the search for new antibody‐based therapies against various cancers.